A Case Report of Acute Severe Myelitis and Meningitis Secondary to Varicella Zoster Virus Reactivation in a Patient with Acquired Immunodeficiency Syndrome - Victor A. Novelo-Hernández; Marco Cárdenas; Claudia Torres-González; Patricio Garcia-Espinosa; Rómulo Ramirez; Marco Díaz-Torres; Alejandro Marfil-Rivera (University Library System, University of Pittsburgh, 2021)
Background: Myelitis post Herpes-Zoster is a rare condition that is typically associated with immunocompromised states. It usually starts as an acute loss of sensory and motor functions below the affected spinal cord level. The condition can range in severity from a mild to a fatal presentation. Other neurological complications include meningitis, atypical presentations should encourage the search for undiagnosed immunosuppression states. The Case: We describe the case of a 42-year-old man, with previously undiagnosed HIV, who developed acute myelitis and meningitis after the appearance of the classic zoster lesions. On lumbar puncture and subsequent CSF analysis, the patient was found to have Froin's Syndrome. The patient was initiated with ceftriaxone, vancomycin, and acyclovir regimen and prophylactic antiphymic treatment was also added. After 14 days in the hospital, the fever, headache, and neck stiffness subsided while the sphincter function and lower limb paraplegia did not improve. Conclusion: Varicella zoster virus reactivation suggests underlying immunosuppression. This case demonstrates the importance of being cognizant to the wide range of clinical manifestations that may suggest spinal cord involvement after clinical reactivation. Furthermore, physicians also need to be mindful that Acquired Immunodeficiency Syndrome (AIDS) and other immunodeficiency states could present with atypical clinical manifestations.